Under Water to Outer Space Augmented Reality for Astronauts and Beyond - Nuernberger, Benjamin (IEEE computer graphics and applications, 2020)
Augmented reality (AR) has the potential to help astronauts execute procedures in a quicker, more intuitive, and safer way. A key part of realizing these benefits has been the use of an undersea research facility-the Aquarius-that acts as an analog to the International Space Station to a certain extent. In a June 2019 mission, the Aquarius crew successfully executed a complex procedure taking place across four different task areas by using an AR application called ProtoSpace developed at the Jet Propulsion Laboratory. In this article, we share the detailed results of the study, lessons learned, and future work needed to further enable the enhancement of procedure execution through augmented reality